Foreign Ownership Effect to Stock Market Liquidity in Indonesia - Annisa Yasmin (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background – One of economic indicators of a country is the capital market. Liquid capital market can attract investors, both foreign and domestic investors, to invest their ownership in that country, which in turn can improve the country’s economic growth. Aim – This research aims to examine the influence foreign ownership on stock market liquidity in Indonesia. Design / methodology / approach – This research splits foreign ownership into two groups, the first one is foreign ownership by financial institutions, and the second one is foreign ownership by non-financial corporations. The type of data used is panel data using fixed effect model (FEM). The technique for examining the influence of foreign ownership on liquidity used multiple regression analysis. Findings – The result found that foreign ownership by financial institutions and non-financial corporations negatively affect liquidity. The study also found a positively non-linear effect between foreign ownership by financial institutions to liquidity and a negatively non-linear effect between foreign ownership by non-financial institutions to liquidity. Research implication – This research can assist investors in determining investment in the Indonesian capital market by pay attention to variables such as foreign ownership, return, turnover, market capitalization and standard deviation. Limitation – The research period was short, which was only 21 months due to limited data and the research period that has passed too long, that is January 2012 to September 2013.